Discovery in the caves of Guangxi, China: three new troglobitic species of Tribasodites Jeannel (Coleoptera, Staphylinidae, Pselaphinae) - Yin, Zi-Wei; Li, Li-Zhen; Zhao, Mei-Jun (Zootaxa, 2011)
Three new species of Tribasodites Jeannel are described and illustrated based on recently collected material in the caves of Guangxi Province: T. bedosae Yin and Li, sp. n., T. deharvengi Yin and Li, sp. n. and T. tiani Yin and Li, sp. n. A key to Chinese troglobitic pselaphine species and a checklist of Tribasodites are presented.